The Traditions of Mummers, Court Masquerades, and Secular Balls - Sokolova, Alla (Journal of History Culture and Art Research, 2020)
The article examines the origins of the traditions of mummers, which are closely related to pagan beliefs and rituals, the cult of the Sun, solar symbols, traditions of the Greeks, Egyptians, Persians, as well as the Roman Saturnalia and the Scandinavian Yule. The tasks and functions of mummer’s rituals are revealed, which are protective, symbolic-mythological, solar-symbolic, magical, imitative, instructive, and pedagogical, as well as an erotic character associated with "human fertility." Wearing a mask or disguise, dressing up in animal skins and in costumes of the opposite sex filled the human personality with new content, sacred meaning, and broadcast the concept of “not - I” or “I am different” to the world. The main rituals of the Slavs associated with dressing (Svyatki and Kolyada), which are a hybrid of pagan and Christian Orthodox traditions, have been determined and characterized. Vechernitsa is specific Ukrainian entertainment, an obligatory attribute of winter Svyatki. The main functions of Vechernitsa are entertainment, sexually developing, sacred, and protective. The Slavic phenomenon of foolishness is considered, which manifested itself as a sacral clowning, a voluntary renunciation of worldly life, and dressing up for the glory of God. The extremely negative attitude of the Orthodox Church to the rituals associated with dressing up and mummering, fortune telling, games, and other kinds of entertainment was determined. A number of prohibitive decrees emanating from the Orthodox clergy did not have the proper effect, since winter rites were becoming part of the culture of the Slavs. Ritual permeated the culture of the Cossacks of the Zaporizhzhia Sich, despite the fact that religion occupied an important place in their lives, enriching it with a high meaning. In the Middle Ages, masquerade penetrates into aristocratic circles and is gradually reborn into the salon-secular style and presupposes the complementarity of two cultural traditions - Western European and native Slavic. The court masquerade balls demonstrate a close connection with the archaic theater, the genre of the English court Masque, the French court ballet, and the Italian intermezzo.